Performance Analysis of Stationary and Deterministic AODV Model - G, Kothai; E, Poovammal (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Vehicular Adhoc Network (VANET) is an emerging technology that provides a digital communication among vehicles, persons and Road-Side Units (RSU). VANETs are highly vulnerable to cyber-attacks. These cyber-attacks make a wrong illusion on traffic jam, can inject false information regarding traffics and injects large amount of spam messages that disrupts the normal functionalities. The main objective of the research work is to implement and analyze the different models that help in improving the traffic management. The scenarios are simulated, and the performance is analyzed using the OMNET++ Simulator.